Pengaruh Perkembangan Sektor Perdagangan, Hotel Dan Restoran Kota Bandung Terhadap Sektor Pertanian Daerah Lainnya di Jawa Barat - Dariah, Atih Rohaeti; Sundaya, Yuhka (Jurnal Ekonomi Kuantitatif Terapan; 2012: Vol. 5, No. 2, Agustus 2012 (pp. 79-150), 2012)
This paper studied the influence of trade, hotels and restaurants (THR) sector growth of Bandung to other agricultural area in West Java Province. It will reflect the urban and rural economic linkages through production linkages. The methods used are simultaneous equations which are estimated by Seemingly Unrelated Regression (SUR) technique, because each district/city agricultural GDRP described by the same explanatory variables i.e: trade, hotels and restaurants of Bandung. The results are quite adequate for interpretation, reflected in the sign coefficient score responding to the hypothesis, the amount of R 2 , and t test statistic with the amount of under 0.5. The conclusion indicated that the trade, hotels and restaurants of Bandung were more encourage agricultural area that located far enough from Bandung city, such as Garut, Tasikmalaya, Subang, Cianjur, Sukabumi, Indramayu and Cirebon District. All districts are center of production of crops, livestock and fisheries.
Keywords: THR sectors; agricultural; economic linkages; SUR method